Theoretical Estimation of the Autocorrelation Postulate for Nonlinear Sequences Generated from Threshold (Journal of the College of Basic Education, 2023)
The Randomness is one of the basic criterions to measure Key Generator Efficiency. The key generator depends basically on Linear FeedBack Shift Register which is considered as one of the basic units of Stream Cipher Systems. In this paper, the autocorrelation postulate, which one of the basis of Randomness criteria, is calculated theoretically for non-linear key generator before it be implemented or constructed (software or hardware), this procedure save time and costs. A nonlinear key generator is chosen to apply the theoretical studies, this key generator is the Threshold.